Slight changes in the mechanical stimulation affects osteoblast- and osteoclast-like cells in co-culture - Kadow-Romacker, Anke; Duda, Georg N.; Bormann, Nicole; Schmidmaier, Gerhard; Wildemann, Britt (Transfusion medicine and hemotherapy, 2013)
SummaryBackground: Osteoblast- and osteoclast-like cells are responsible for coordinated bone maintenance, illustrated by a balanced formation and resorption. Both parameters appear to be influenced by mechanical constrains acting on each of these cell types individually. We hypothesized that the interactions between both cell types are also influenced by mechanical stimulation. Methods: Co-cultures of osteoblast- and osteoclast-like cells were stimulated with 1,100 µstrain, 0.1 or 0.3 Hz for 1-5 min/day over 5 days. Two different setups depending on the differentiation of the osteoclast-like cells were used: i) differentiation assay for the fusion of pre-osteoclasts to osteoclasts, ii) resorption assay to determine the activity level of osteoclast-like cells. Results: In the differentiation assay (co-culture of osteoblasts with unfused osteoclast precursor cells) the mechanical stimulation resulted in a significant decrease of collagen-1 and osteocalcin produced by osteoblast-like cells. Significantly more TRAP-iso5b was measured after stimulation for 3 min with 0.1 Hz, indicating enhanced osteoclastogenesis. In the resorption assay (co-culture of osteoblasts with fused osteoclasts) the stimulation for 3 min with 0.3 Hz significantly increased the resorption activity of osteoclasts measured by the pit formation and the collagen resorption. The same mechanical stimulation resulted in an increased collagen-1 production by the osteoblast-like cells. The ratio of RANKL/OPG was not different between the groups. Conclusion: These findings demonstrate that already small changes in duration or frequency of mechanical stimulation had significant consequences for the behavior of osteoblast- and osteoclast-like cells in co-culture, which partially depend on the differentiation status of the osteoclast-like cells.